Simbol dalam Tradisi Kematian (Geblag) Masyarakat Jawa di Desa Tamankuncaran Kecamatan Tirtoyudo Kabupaten Malang - Oktalia, Aurora Indah; Novariyanto, Rizki Agung (Ideas Publishing, 2024)
The geblag tradition has rich and complex cultural values, reflecting the beliefs, hopes and social relations of the local community. The main aim of the research is to reveal the symbols of the geblag death tradition in Tamankuncaran Village. The type of research used is qualitative with a descriptive approach, with data collection in the form of observation, interviews, documentation and library research methods. The results of the research show that the geblag tradition has a symbol, these symbols are, first the symbols in the offerings are water (in which there are flowers), coffee, tea, cigarettes, kinang, food that the deceased liked and market snacks. The second is a symbol of the grave pilgrimage of performing ablution, saying hello, cleaning the grave and scattering flowers.